KEPUASAN KERJA PEDAGANG PASAR KAGET DI RW 15 KELURAHAN SIMPANG TIGA KECAMATAN BUKIT RAYA KOTA PEKANBARU - Sari Oktavia Oktavia; Sumardi '; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the level of job satisfaction the kaget market traders in Rw 15 Simpang Tiga Village District Bukit Raya Pekanbaru. The research questions guiding this study is: how high levels of job satisfaction the kaget market traders in Rw 15 Simpang Tiga Village District Bukit Raya Pekanbaru. This is a descriptive study, data were collected using a questionnaire totaling 33 point statement. Once tested, the questionnaire of 26 items declared valid, invalid and of 7 items. Otherwise the entire legal instruments with "rhitung = 0.444 means that legitimacy is quite high. The population in this study was 48 the kaget market traders. The samples were taken using simple random sampling method using Taro Yamane formula. Based on the findings obtained job satisfaction the kaget market traders Rw 15 at Simpang Tiga District Bukit Raya Pekanbaru the pleasant feeling of respondents who was the level satisfaction of work high  is  89.78% and the low level of work satisfaction is 10.16%. According to the respondents unpleasant feeling that the level of work satisfaction high and 85,93% low levels of work satisfaction of 14.05%. Keywords: Job Satisfaction, The Kaget Market